The Prediction of Surgery Outcomes in Abdominal Tumor Patients with Sepsis by Pcv-aCO2/Ca-cvO2 - Lyu Y; Han T; Liu M; Cui K; Wang D (Dove Medical Press, 2022)
Yang Lyu,1,* Tao Han,1,* Meirong Liu,2 Keliang Cui,1 Donghao Wang1 1Department of Intensive Care Unit, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin's Clinical Research Center for Cancer, Tianjin, People's Republic of China; 2Department of Infectious Diseases, Tianjin Hospital, Tianjin, People's Republic of China*These authors contributed equally to this workCorrespondence: Donghao Wang, Department of Intensive Care Unit, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin's Clinical Research Center for Cancer, West Huan-Hu Rd, Ti Yuan Bei, Hexi District, Tianjin, 300060, People's Republic of China, Email donghaow@tom.comBackground: To determine whether Pcv-aCO2/Ca-cvO2 combined with Pcv-aCO2 could predict the outcomes in patients complicated with abdominal infection and sepsis after abdominal tumor operation.Methods: Total 92 patients admitted to our hospital from January 2017 to December 2020 who underwent abdominal tumor operation were enrolled. Blood gas analysis of artery and central vein, various laboratory indexes, SOFA score, hemodynamic parameters at different time points and treatment outcome were recorded.Results: ROC curve analysis showed that hemodynamic parameter alone could not predict ICU treatment outcome and mortality of patients, but 72-hour SOFA score could predict treatment outcome of patients (AUC = 0.930, 95% CI: 0.803- 1.000, p = 0.019). The significant hemodynamic parameter for evaluating treatment outcome and prognosis of patients was Pcv-aCO2 + Ratio of T3. Kaplan-Meier univariate survival curve and Log-rank suggested that patients who had higher combined predictive parameter of T3 Ratio + T3 Pcv-aCO2 still had ischemia and hypoxia of tissues and organs after standard fluid resuscitation, and treatment outcome was not good. In subgroup analysis, patients with higher Ratio had higher lactate, higher T72 SOFA score, and poor treatment outcome.Conclusion: The combination of Ratio and Pcv-aCO2 could evaluate clinical treatment outcome of patients complicated with abdominal infection and sepsis after abdominal tumor operation.Keywords: ratio, Pcv-aCO2, Ca-cvO2, sepsis, hemodynamic, abdominal tumor